AKUNTANSI PEMBIAYAAN QARDHUL HASAN PADA BANK SYARIAH BERDASARKAN PSAK 59 (Studi pada Bank Aceh Syariah Banda Aceh) - Rahayu, Riskia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This research was conducted at Bank Aceh Syariah Banda Aceh which was one Islamic bank in Banda Aceh received the funds performed by qardhul hasan financing. The purpose of this study was to determine whether the accounting treatment is the recognition, measurement, presentation, and disclosure of source and uses of funds qardhul hasan conducted by Bank Aceh Syariah Banda Aceh has been in accordance with PSAK 59.